2020
DOI: 10.3390/cancers12051238
|View full text |Cite
|
Sign up to set email alerts
|

Y RNA: An Overview of Their Role as Potential Biomarkers and Molecular Targets in Human Cancers

Abstract: Y RNA are a class of small non-coding RNA that are largely conserved. Although their discovery was almost 40 years ago, their function is still under investigation. This is evident in cancer biology, where their role was first studied just a dozen years ago. Since then, only a few contributions were published, mostly scattered across different tumor types and, in some cases, also suffering from methodological limitations. Nonetheless, these sparse data may be used to make some estimations and suggest routes to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 95 publications
0
18
0
Order By: Relevance
“…Another interesting smRNA species, Y RNAs, also showed markedly biased expression patterns between LM CSF EVs and HC. The members of this well-characterized smRNA subpopulation act as components of the Ro60 ribonucleoprotein particle, which is a target of autoimmune antibodies in patients with systemic lupus erythematosus [ 33 ]. Y RNAs are also necessary for DNA replication through their interactions with chromatin and initiation proteins [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another interesting smRNA species, Y RNAs, also showed markedly biased expression patterns between LM CSF EVs and HC. The members of this well-characterized smRNA subpopulation act as components of the Ro60 ribonucleoprotein particle, which is a target of autoimmune antibodies in patients with systemic lupus erythematosus [ 33 ]. Y RNAs are also necessary for DNA replication through their interactions with chromatin and initiation proteins [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…These smRNAs are components of the Ro60 ribonucleoprotein particle, which is a target of autoimmune antibodies in patients with systemic lupus erythematosus. These RNAs are involved in various basic intracellular processes, such as DNA replication and RNA quality control [ 33 ]. Several studies have reported the abundant presence of Y RNAs in cell culture EV and body fluids.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we believe that it would be also very interesting to investigate additional potential ncRNA markers that, to date, have not been explored in this cancer, such as YRNA, which might highlight additional actors in EC etiology and would suggest novel potential therapeutic targets [ 238 ]. The genetic and epigenetic characterization of patients could lead to surgical strategies (lymphadenectomy versus sentinel lymph node sampling versus total hysterectomy and bilateral salpingo-ophorectomy), adjuvant therapies (BRT versus EBRT versus chemotherapy), and patients’ surveillance (strict follow up versus watchful waiting strategy).…”
Section: Discussionmentioning
confidence: 99%
“…The loop domain is the least conserved element that regulates chromatin binding. Studies have shown that YRNAs function to initiate chromosomal DNA replication, which is related to cell proliferation (Gulia et al, 2020 ). Christov et al ( 2008 ) found that the expression of all the four YRNAs was dramatically higher in solid tumors relative to corresponding normal tissues.…”
Section: The Emerging Future Of Ncrnas In Angiogenesismentioning
confidence: 99%